下顎骨に発生したエナメル上皮線維肉腫の1例 - 石橋, 美樹; 美馬, 孝至; 岸野, 万伸; 横田, 祐介; 鏡内, 肇; 石井, 庄一郎 (日本口腔外科学会雑誌, 2011)
Ameloblastic fibrosarcoma is a very rare malignant odontogenic tumor. Ameloblastic fibrosarcoma consists of benign epithelial components with the same features as those of ameloblastic fibroma, as well as malignant mesenchymal components. We report a case of ameloblastic fibrosarcoma arising in the mandible. A 32-year-old woman underwent left hemimandiblectomy, supraomohyoid neck dissection, and reconstruction. Immunohistochemically, the Ki-67 labeling index was low in the epithelial components of the tumor （1.6 ％）, but high in the malignant mesenchymal components （19.8 ％）. After operation, adjuvant chemotherapy was administered. There was no recurrence or metastasis 3 years after surgery.